2018
DOI: 10.1024/0300-9831/a000486
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C reverses bone loss in an osteopenic rat model of osteoporosis

Abstract: Abstract. Fruits and vegetables are rich in vitamin C with antioxidant properties which are known to influence bone quality. This study evaluated whether vitamin C (1000 mg/L) added to drinking water reverses the bone loss in ovariectomized rats. Ninety-day-old female Sprague-Dawley rats were randomly assigned to either sham (n = 14) or ovariecotmized groups (n = 28). Sixty days after ovariectomy, the treatments were sham, ovariectomy (OVX), OVX + vitamin C (22 mg oral intake daily) for 60 days. Urine was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the present study, we found that vitamin C contributed greatly and positively to the association of multivitamin coexposure with BMDs. To date, many studies have demonstrated that vitamin C contributes to elevated BMDs [9,15]. Vitamin C can stimulate type 1 and 2 collagen synthesis, limit the lifetime of osteoclasts, and prevent the loss of osteoblast markers [27].…”
Section: Water-soluble Vitamins and Bmdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that vitamin C contributed greatly and positively to the association of multivitamin coexposure with BMDs. To date, many studies have demonstrated that vitamin C contributes to elevated BMDs [9,15]. Vitamin C can stimulate type 1 and 2 collagen synthesis, limit the lifetime of osteoclasts, and prevent the loss of osteoblast markers [27].…”
Section: Water-soluble Vitamins and Bmdmentioning
confidence: 99%
“…Taking all the above evidence, vitamins play critical roles in bone health maintenance. However, most of the existing studies focused on a single or two vitamins at once [13,15]. A drawback in these studies is the lack of understanding of the associations of multivitamin coexposure on bone health due to the simultaneous exposure to multivitamins from diverse sources for individuals in reality.…”
Section: Introductionmentioning
confidence: 99%
“…31 In another study vitamin C reversed the bone-specific changes caused by ovariectomy in rates, including decreased bone quality and antioxidant capacity. 32 Choi et al 9 recently found that vitamin C can inhibit osteoporosis by promoting osteoblast formation and inhibiting osteoclastogenesis via multiple signaling pathways in ovariectomized (OVX) Wistar rats. 9 Their results also revealed that vitamin C supplementation led to improved bone mineral density (BMD) and bone volume, a higher number of osteoblasts and osteoclasts, and increased expression of osteoblast differentiation genes in OVX rats.…”
Section: Bone Healing and Osteoporosismentioning
confidence: 99%
“…In this study, both groups all had a complete bone union at 6 weeks 31 . In another study vitamin C reversed the bone‐specific changes caused by ovariectomy in rates, including decreased bone quality and antioxidant capacity 32 . Choi et al 9 recently found that vitamin C can inhibit osteoporosis by promoting osteoblast formation and inhibiting osteoclastogenesis via multiple signaling pathways in ovariectomized (OVX) Wistar rats 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because osteoporosis commonly affects women in the post-menopausal age, ovariectomized rodents are operative models for studying its pathogenesis and therapeutic interventions [31]. Interestingly, oral vitamin C supplementation following ovariectomy in mice was shown to be protective against bone loss and osteoblast depletion [32,33]. Vitamin C intake resulted in an increased expression of osteoblast differentiation genes in time [32], suggesting that vitamin C could stimulate bone formation by inducing maturity and mineralizing osteoblast phenotype.…”
Section: Studies On Animal Modelsmentioning
confidence: 99%